Characterization of In Vitro DNA Binding Sites of the EUO Protein of Chlamydia psittaci - Zhang, Li (American Society for Microbiology, 2000)
The EUO gene of chlamydia is highly expressed early in the developmental cycle, relative to other genes, but continues to be expressed throughout the active growth phases. The precise function of EUO protein is not known, but it binds to DNA in vitro. In this study, we developed a selection and amplification scheme for identifying chlamydial genomic fragments to which EUO preferentially binds in vitro. The scheme involved mixing recombinant EUO with a Chlamydia psittaci genomic library in a pBluescript plasmid vector in vitro, trapping EUO-bound plasmid clones on filters, and amplifying the clones in Escherichia coli. After nine rounds of enrichment, the EUO binding sites of the three most highly enriched clones were identified by DNase I footprint analysis. All three clones had multiple binding sites of various sizes with no clear distinguishing feature other than they were AT-rich and were usually not located in putative promoter regions. We used limited site-specific mutagenesis to characterize the strongest binding site of the most-highly-enriched clone, which represented about 50% of the population after nine rounds. This mutagenesis identified a core binding site of 15 nucleotides (nt) whose sequence was used to find related sequences within each of the strong binding sites in the other two clones. Using the frequency of bases at specific positions within this group of sequences as a guide, we carried out trial-and-error searching with many related sequences, eliminating those which identified nonfootprinted sites. This process led us to the consensus 15-nt sequence AHGAAAWVTYTWDAY, which, when allowing two mismatches, picked out all of the strong binding sites and no nonfootprinting sites within the three enriched clones. This sequence may be useful for predicting additional possible EUO binding sites in the chlamydial genome.